Genetic variants in the leptin-melanocortin pathway and their joint effects with physical activity and sleep duration on risk of childhood obesity - Xiaotong Liang; Shun Pan; Jiting Ji; Yuying Deng; Miao Chen; Ziwei Huang; Jiaru Deng; Min Chen; Tiantian Xiong; Jianping Liang; Li Liu (PLoS ONE, 2026)
Objective This study aimed to investigate the associations between functional genetic variants in leptin-melanocortin pathway and risk of childhood obesity, as well as exploring gene-lifestyle interactions on obesity risk. Methods A frequency-matched case-control study included 1123 children and adolescents with obesity and 1231 controls from Guangzhou, China. Twelve potentially functional genetic variants were genotyped. Multivariate logistic regression and classification and regression tree were applied to identify obesity-associated genetic variants. Unweighted and weighted genetic risk scores (GRSs) were constructed, and their interactions with physical activity and sleep were assessed using relative excess risk of interaction ( RERI ), attributable proportion of interaction ( AP ) and the interaction of odds ratio ( IOR ). Results We identified important genetic variants associated with obesity: MC4R rs17782313, rs12970134, LEPR rs1137101, and POMC rs6713532. High unweighted GRS was associated with a higher obesity risk than low GRS ( OR = 1.40, 95% CI = 1.09–1.79), with similar results for the weighted GRS. High unweighted GRS combined with inadequate sleep or physical activity conferred increased risk of obesity compared to low/medium GRS with healthy lifestyle ( OR = 1.70, 95% CI = 1.28–2.26; OR = 1.59, 95% CI = 1.17–2.17). However, the 95% CI s for all RERI s and AP s contained 0, and for IOR s contained 1, suggesting no significant interaction. Conclusions Four genetic variants in the leptin-melanocortin pathway are associated with the risk of obesity, both individually and jointly. Furthermore, the joint effect of these genetic variants with inadequate sleep and physical activity may contribute to obesity development in children and adolescents.